Mother's Knowledge and Behaviour Towards Oral Health During Pregnancy - Anandina Irmagita Soegyanto; Ratu Nabila Larasati; Yuniardini Septorini Wimardhani; Buğra Özen (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the knowledge and behaviour of mothers in maintaining their oral health during pregnancy. Material and Methods: This study included 167 women in five community primary health centres in Central Jakarta whose last child ranged between 0-59 months. The participants were asked to fill the questionnaire "Knowledge and Behaviour Towards Oral Health during Pregnancy" (KBOHP). This questionnaire assessed the knowledge and behaviour in maintaining oral health during pregnancy. Results: Almost 80% of participants reported that they had government dental health coverage. Only about 16% of participants reported that they visit dentist before pregnancy and only about 32% of the participants reported to have oral health problems during pregnancy. Although they have oral health problems, only 18% of them visited the dentists during pregnancy. Only 33% of the participants knew that the periodontal problems can affect pregnancy outcome, and 54.5% of participants had never heard of a possible connection between oral health and pregnancy. About 74% of participants reported that they never had specific oral health care instruction during pregnancy. Participants who received oral health instruction from their health providers also tend to have dental visit during pregnancy. Conclusion: Knowledge and behaviour towards oral health during pregnancy in this population was still low. A program that is developed to improve knowledge and behaviour in maintaining oral health during pregnancy is needed.